What to expect when you are expecting : maternity leave and female labor market outcomes (2021)
In 2017, the leave period to which all female workers are entitled to around childbirth increased from 14 to 18 weeks in Colombia. This article analyzes the impact of the reform that extended the maternity leave period on mothers' labor market outcomes after childbirth. To identify the causal impact of the reform, we use a difference-in-difference design to compare labor market outcomes of mothers who gave birth before the change in the maternity leave legislation to mothers who gave birth after. We use administrative data from the Social Security System to estimate the intent-to-treat effect of the reform on mothers' employment continuity, earnings, and the probability of working in a female-dominated (or pink-collar) sector after childbirth. Results suggest that the extension increases the probability that eligible mothers had left the formal labor market 2, 3, 4, and 5 months after the maternity leave by approximately 2 percentage points but has no effect on their probability of leaving the pre-birth employer for another job within formality. Results also suggest the reform increases the probability that eligible mothers work in a pink-collar sector 2, 3, 4, and 5 months after the maternity leave. Furthermore, we find that the extension decreases eligible mothers' post-birth earnings.